A Evolução da Carpintaria na Arquitectura - Cláudia Malhadas Sousa (2014)
The storytelling wood.It's veins inform us of it's age, grading reflects the care put into it (or lack of), and color reveals how much sun exposure it actually got.By wandering the streets of Oporto, we are confronted with centuries of Architectural history on which wood maintains it's dominating role throughout the years. One can also perceive that Artisans lost the spotlight they once had. The shifting trends towards increasing machine usage changed construction habits and developed the usage of premade standardized elements. The appearance of new architectural materials such as concrete, steel and glass, by the turn of the twentieth century also provoked a reduction of wood usage on modern construction.This self-proposed task has the purpose of exploring the evolution and metamorphose of carpentry techniques and wood employment on residential architecture. On the seventeenth and eighteenth centuries handmade designs reigned while on the twentieth and twenty first centuries a geometrical drawings prevail above else.Noteworthy that this doesn't mean a lack of diversity, the variety was relocated to the detailing and techniques played by the Architect will.